A EMERGÊNCIA DA ÉTICA SOCIOAMBIENTAL E A QUESTÃO DOS TRANSGÊNICOS - Barreto Ferreira de Oliveira, Kátia Cristina; Becker, Evaldo (Prometheus - Journal of Philosophy., 2020)
This article aims to analyze socio-environmental ethics in the technological age from its modern roots. Based on the theoretical framework centered on modern and contemporary thinkers, reflections on the concepts alluding to socio-environmental ethics were used, based on an interdisciplinary approach. In this context, the origins of a technological thought and its implications in relation to nature and man himself were discussed. Finally, some ethical questions related to the production of transgenic plants will be analyzed, in favor of an ecologically balanced environment for present and future generations.Among the main authors used to deepen the issues pertaining to Socio-Environmental Ethics and its modern origins are: Rousseau (1754), Condorcet (1993); Larrère and Larrère (1997); Jonas (2006); Singer (2006); Vázquez (2010); Parizeau (2007); Leopold (1949). Regarding the ethical reflections related to the release of transgenic plants into the environment, works by authors such as: Lacey (2006a, 2008, 2010) and Ferment (2015) were analyzed.